Elaborating the urbanism in smart urbanism: distilling relevant dimensions for a comprehensive analysis of Smart City approaches. Issue 9 (29th July 2019) - Verrest, Hebe; Pfeffer, Karin
ABSTRACT: Over the last decade, Smart City has increasingly become a popular urban policy approach of cities in both the Global North and Global South. Such approaches focus on digital and technology-driven urban innovation and are often considered to be a universal solution to varied urban issues in different cities. How Smart City policies operate in contemporary cities is being examined in the emerging, but still underdeveloped, academic field 'smart urbanism'. The considerable consequences of Smart City strategies call for critical engagement with the rationale, methods, target group and implications of Smart City approaches in different urban contexts. The aim of this paper is to further such critical engagement by distilling dimensions absent in current smart urbanism. We do so by exploring both the academic field of critical urbanism and smart urbanism and through that develop our contributions to the smart urbanism debate from existing theoretical and conceptual approaches within critical urbanism. We distilled three dimensions that require further development to facilitate a comprehensive analysis of what Smart City policies mean for contemporary urban life: (1) the acknowledgement that the urban is not confined to the administrative boundaries of a city; (2) the importance of local social-economic, cultural-political and environmental contingencies in analysing the development, implementation and effects of Smart City policies; and (3) the social-political construction of both the urban problems Smart City policies aim to solve and the considered solutions. As such, we argue that there is a lack of consideration for 'the urbanism' in smart urbanism.